A novel Alu-mediated microdeletion at 11p13 removes WT1 in a patient with cryptorchidism and azoospermia - Seabra, Catarina M. (2015)
This article describes a patient with cryptorchidism and nonobstructive azoospermia presenting a novel microdeletion of approximately 1 Mb at 11p13. It was confirmed by multiplex ligation-dependent probe amplification that this heterozygous deletion spanned nine genes (WT1, EIF3M, CCDC73, PRRG4, QSER1, DEPDC7, TCP11L1, CSTF3 and HIPK3) and positioned the breakpoints within highly homologous repetitive elements. As far as is known, this is the smallest deletion as-yet described encompassing the WT1 gene and was detected only once in a total of 32 Portuguese patients with isolated uni- or bilateral cryptorchidism. These findings suggest that molecular analysis in patients with genitourinary features suggestive of WT1 impairment, namely cryptorchidism and renal abnormalities, may reveal cryptic genetic defects.